Laparoscopic resection of a large adrenal myelolipoma: a case report - Ghatak, Supriyo (BioMed Central, 2009)
A 53 year man presented with pain right upper quadrant for seven months. On evaluation he was found to have a large right adrenal myelolipoma. Laparoscopically by transperitoneal right flank approach this was removed. Postoperative recovery was uneventful. Operative specimen's histopathological examination confirmed the diagnosis of adrenal myelolipoma.